Pengaruh model pembelajaran problem based learning (PBL) berbantuan media flashcard terhadap keterampilan berpikir ilmiah peserta didik pada pembelajaran IPAS - Chaerinna Chaerinna; Yenny Indrastoeti Siti Purwanti; Chumdari Chumdari (Universitas Sebelas Maret, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by Flashcard media on scientific thinking skills in science learning for grade IV students of Indonesiaku Kaya Budaya. The study used a quantitative approach with a quasi-experimental research type. The research sample consisted of 3 schools, namely SD Negeri Wonokerso 1, SD Negeri Wonokerso 2 and SD Negeri Wonokerso 3. Sampling was carried out using the cluster random sampling technique. The research design used a pretest posttest control group design. Data collection was carried out using essay test techniques to measure students' scientific thinking skills and observation to obtain information on the implementation of the problem based learning model. The validity test technique used Aiken V validity and instrument trials on grade IV students of SD Negeri Wonokerso 2. Data analysis used inferential analysis techniques. The results of this study indicate a positive and significant effect of the application of the problem based learning (PBL) model on students' scientific thinking skills. The results of the hypothesis test using the t-test obtained an asymp.sig value of 0.007 or less than the significance level of 0.05. Based on the results of the study, it can be concluded that the application of the problem based learning (PBL) model assisted by Flashcard media has a positive and significant effect on students' scientific thinking skills.